Conceptual Overview of Lander Taxes and Their Social , Economic and Ecological Impact (2015)
In Colombia and in accordance with the law applicable to municipalities and regional authorities, there is a regional legislative autonomy in tax matters, which are governed from certain conceptual bases and have stated objectives in order to bring welfare to the population. A description and analysis of the conceptual foundations and objectives in determining territorial tax basis, could give the ordinary citizen a greater understanding of the importance of this legislative task in the economic, ecological, political and social development of the community.